Code-switching Among Adult Bidayuh Singai/Jagoi Community In Their Daily Conversation - Laura, Salin (Universiti malaysia sarawak (UNIMAS), 2008)
The study looks at the phenomenon of code-switching among adult Bidayuh Singai/Jagoi community in their daily conversation within the family domain that involves the same Bidayuh speakers. The study aimed at identifying the languages used by the respondents, finding the level at which code-switching occurs, discerning who the respondents' code-switch with and describing the respondents' reasons for code-switching in their daily conversation. A case study was carried out using observation and tape-recording. A total of 20 respondents from five Bidayuh Singai/Jagoi families from five different kampongs in the Bau District, made up the samples of the study. The findings reveal that code-switching occur mostly among adults family members who are below 65 years of age. The languages used during code-switching are Dialek Melayu Sarawak and English. Code-switching happens at three different levels; word, phrase and sentence level. Besides that, this study also determine the reasons why they code-switch among themselves.